LITERATURE REVIEW: HUSBAND'S ROLE IN REDUCE THE INCIDENCE OF POSTPARTUM DEPRESSION IN WORKING WOMEN IN INDONESIA - Linda Wahyuni Putri (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Postpartum stress conditions are experienced by most women. Mothers who are actively working tend to have a greater risk of Postpartum Depression than mothers who do not work. This is due to the dual roles of raising children, managing the household, and completing work matters. This study aimed to determine husbands' support for the incidence of Postpartum Depression in working women in Indonesia. This study used a literature review strategy that was reviewed from several sources such as PubMed, ScienceDirect, and Google Scholar with a selection of articles published from 2017 to 2023. Searches in the database were carried out using keywords such as “Postpartum Depression”, “Working Women and Postpartum Depression”, and “Husband’s Role and Postpartum Depression”. The literature review results show that the main factor influencing the incidence of Postpartum Depression in Working Women is the lack of a husband's role. Based on the literature review, it can be concluded that family support, especially husbands, is needed to minimize Postpartum Depression in Working Women. It is hoped that husbands will support and help working women in taking care of their children so that Postpartum Depression does not occur.